2006
DOI: 10.1136/bjo.2006.094433
|View full text |Cite
|
Sign up to set email alerts
|

Changing pattern of childhood blindness in Maharashtra, India

Abstract: Aim: To determine the causes of severe visual impairment and blindness in children in schools for the blind in Maharashtra, India. Methods: Children aged ,16 years with a visual acuity of ,6/60 in the better eye, attending 35 schools for the blind were examined between 2002 and 2005, and causes were classified using the World Health Organization's system. Results: 1985 students were examined, 1778 of whom fulfilled the eligibility criteria. The major causes of visual loss were congenital anomalies (microphthal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 16 publications
7
68
4
Order By: Relevance
“…That the critical period of surgery for unilateral congenital cataract is 6 weeks of age is a well-known fact, and permanent sensory deprivation can occur if surgery is delayed beyond 4 months of age in bilateral dense cataract. 19 In our study, the lensrelated disorders accounted for 17.2%, being nearly similar to Thailand (16.9%) 10 and Indonesia (16.4%).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…That the critical period of surgery for unilateral congenital cataract is 6 weeks of age is a well-known fact, and permanent sensory deprivation can occur if surgery is delayed beyond 4 months of age in bilateral dense cataract. 19 In our study, the lensrelated disorders accounted for 17.2%, being nearly similar to Thailand (16.9%) 10 and Indonesia (16.4%).…”
Section: Discussionmentioning
confidence: 68%
“…Similarly affected family members were seen in 21% of the children almost similar to a study from India. 10 The majority of them (n ¼ 323, 68.9%) were blind (best corrected visual acuity (BCVA) in the better eye of o3/60). No statistical difference in visual impairment categories was observed between the two education systems (P ¼ 0.06, 2 d.f.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is relatively less in magnitude when compared to the recent finding from Maharashtra. 8 No child in our study was found to be blind due to retinopathy of prematurity (ROP). Though, this finding concurs with a recently published report from Maharashtra, 8 however, ROP is found to be reaching epidemic proportions and becoming a public Visual impairment among children in schools for the blind S Krishnaiah et al health problem not only in India but also in many middle income countries.…”
Section: Discussionmentioning
confidence: 95%
“…The finding of higher rates of microphthalmos and anophthalmos has been found to be a common finding in many studies conducted earlier on blind children in India. 3,4,7,8,14,15 Congenital ocular anomalies were responsible for major causes of blindness in 41.3% and 27.4% of children in Maharashtra and Delhi, respectively. Retinal blindness was the second most common cause of SVI/BL (18.9%; n ¼ 21) identified in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation